Development of a 3D Gait Measurement Protocol for Amputees Walking on Treadmill - Mahyuddin, Andi Isra; Ferryanto, F; Herman, Indria; Mihradi, Sandro; Dirgantara, Tatacipta (Mesin, 2017)
Walking motion is actually a complex activity since it involves many body parts, especially the lower limb. Due to the needs for gait analysis in many medical applications, Biomechanics Research Team at ITB has developed an affordable optical motion analyzer to measure motions of subject walking over ground. However, the needs for multicycles gait data is better met by measuring subjects walking on treadmill. This paper discusses the modification of the developed motion analyzer to accommodate data acquisition of subject walking on treadmill, including those of transfemoral amputees. Seven markers, two 95 fps cameras, a dual-channel Camera Link Acquisition NI PCIe-1430 frame grabber, and a workstation are employed in the optical motion analyzer system. The speed displayed on the treadmill is evaluated. Additional equipment such as the modified hydraulic engine crane and the body harness are introduced to ensure the safety of amputees and avoid the risk of falling down while walking on the treadmill. The modified motion analyzer system is then used to obtain gait parameters of normal (37 males and 31 females) and three amputee subjects. The gait parameters of normal subjects in the treadmill walking shows that there is a decrease in the stride length and range of motion, and increase in the cadence due to walking adaptation. There are also phase shifting and increase in the range of motion for amputee subjects compared to the normal subjects which imply that there is an extra work done by the residual limb in doing walking movement and the amputee subjects try to balance their walking on the treadmill.